Analisis Resiliensi Sistem Sosial-Ekologi (SES) Masyarakat Pesisir di Distrik Merauke dan Naukenjerai, Merauke-Papua Selatan - Untari, Untari (MuJAgri: Musamus Journal of Agribusiness, 2023)
The one community of people who are vulnerable to poverty in Merauke are people who live in coastal areas who depend on the availability of natural resources for their livelihoods, namely the ecology of coastal areas from fisheries and non-fishery sectors. Community behavior in an area can form new behaviors while still prioritizing local wisdom to maintain ecological, social and economic functions and improve community welfare. The aim of the research is to identify groups of community who are vulnerable to poverty in order to increase the socio-ecological resilience of communities in coastal areas by using a qualitative descriptive research approach using the case study method. The research was conducted on community groups in coastal areas, namely groups of traditional fishermen or small fishermen. The resilience analysis focuses on 4 community vulnerability indicators. The results of the study concluded that the fishermen group has a higher level of resilience to change and uncertainty compared to the farmer group and the service sector. Creating new sources of livelihood for people who are classified as vulnerable groups and restoring the biophysical functions of the coastal environment can increase the resilience of communities in coastal areas. To implement it, a real commitment from all parties is needed by involving coastal communities in planning, implementing and evaluating coastal area management systems to improve people's welfare in a sustainable manner.